Strategies for dealing with hemolyzed samples in regulated LC–MS/MS bioanalysis. (November 2012) - Tang, Daniel; Thomas, Elizabeth
There is a consensus in industry that there is a need to assess the impact of hemolysis on the bioanalytical method. However, due to the difficulty to prepare standardized hemolyzed QC samples and the fact that no apparent conclusion can be made from hemolysis assessments during method validation, we propose that the assessments are conducted during method development and sample analysis. The use of a stable-labeled internal standard is highly recommended to identify the hemolyzed samples with potential issues of matrix effects. When an internal standard response is abnormal, dilution or standard addition can be used to confirm the data accuracy of the hemolyzed samples. An incurred sample reanalysis test is also recommended for hemolyzed samples to ensure the reproducibility of a hemolysis-'insensitive' method. The number of hemolyzed samples selected for incurred sample reanalysis is study dependent. All these additional steps can determine the 'reportability' of the bioanalytical data. For regulated studies, it is important to document all hemolysis tests in appropriate ways based on GLP requirement.